2016
DOI: 10.5056/jnm15178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of DA-9701 (Motilitone) in Functional Dyspepsia Compared to Pantoprazole: A Multicenter, Randomized, Double-blind, Non-inferiority Study

Abstract: Background/AimsThe effect of proton pump inhibitors (PPI) in Asian functional dyspepsia (FD) patients has not been well established as in Western countries. DA-9701, a novel prokinetic agent, stimulates gastric emptying and modulates visceral hypersensitivity in vivo and in human studies. This study was conducted to compare the efficacy of DA-9701 with a conventional PPI in mono or combination therapy in patients with FD. MethodsIn this double-blind, randomized, non-inferiority trial, 389 patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, the actual incidences of the above-mentioned complications are small. The pooled result of two RCTs showed that PPI is significantly more effective than prokinetics for the treatment of functional dyspepsia 197–199. On the balance of risk and efficacy, we conclude that antacids or H2 receptor antagonists are not recommended for the treatment of NSAID-related dyspepsia.…”
Section: Gastrointestinal Effects Of Nsaid Therapymentioning
confidence: 82%
“…However, the actual incidences of the above-mentioned complications are small. The pooled result of two RCTs showed that PPI is significantly more effective than prokinetics for the treatment of functional dyspepsia 197–199. On the balance of risk and efficacy, we conclude that antacids or H2 receptor antagonists are not recommended for the treatment of NSAID-related dyspepsia.…”
Section: Gastrointestinal Effects Of Nsaid Therapymentioning
confidence: 82%
“…In a study in which 389 patients were divided into 3 groups (motilitone-treated, PPI-treated, and PPI with motilitone-treated), all 3 groups showed significant improvement in dyspeptic symptoms and in quality of life measurements. 85 However, there was no difference among the groups except for the status of H. pylori. Of the H. pylori-positive patients, the improvement of dyspeptic symptoms was significantly higher in the PPI alone group or in the PPI with the motilitone group than in the motilitone alone group.…”
Section: Prokineticsmentioning
confidence: 89%
“…Of the H. pylori-positive patients, the improvement of dyspeptic symptoms was significantly higher in the PPI alone group or in the PPI with the motilitone group than in the motilitone alone group. 85 For patients with poor symptom control, increasing the dose of prokinetics or combining 2 types of prokinetic agents, such as metoclopramide and domperidone, was found to be effective. 86,87 Mechanisms, doses, special comments, and adverse effects of prokinetics for FD are summarized in Table 3.…”
Section: Prokineticsmentioning
confidence: 99%
“…The current pharmacologic treatments for patients with FD are limited and unsatisfactory, and a standard management paradigm has not been established . The typical medications used for it include proton pump inhibitors, antacids, antidepressants and anxiolytics and prokinetics, with only limited symptomatic or QoL benefits in some cases .…”
Section: Introductionmentioning
confidence: 99%